The development of E-Portfolio as an effective presentation medium among Art and Design Education students / Nor Aszila Abdul Rahman - Abdul Rahman, Nor Aszila (Faculty of Education, 2014)
The purpose of study was to make the survey of Art and Design Education students from Faculty of Education University Teknologi Mara Shah Alam. The main purpose of this study was to see the development of E-Portfolio as affective medium during presentation. The data obtained from the questionnaire were distributed to the students involve to get the feedback needed for this study. Based on the survey results the developments of E-Portfolio among students are encouraging. The E-Portfolio can be make one of the guideline for the student which is one of the function is to store all the personal record and also it is very useful for apply job purposes. Overall, the E-Portfolio very encouraged based on feedback from the respondent. All the respondent give the positive feedback about the E-Portfolio.